Immunohistochemical study of permeability glycoprotein expression in canine perianal tumors: https://doi.org/10.12982/VIS.2025.071 - Pichaiya, Nutchanon; Matchimakul, Pitchaya; Arunorat, Jirapat; Thongtharb, Atigan (Veterinary Integrative Sciences, 2024)
Perianal gland tumors are androgenic hormone-dependent and commonly found in dogs. Permeability glycoprotein (PGP) is a member of the ATP-binding cassette transporter family, playing an essential role in reducing intracellular drug concentration and limiting drug cytotoxicity in cancer cells, leading to multi-drug resistance. This study aims to investigate PGP expression patterns in perianal gland tumors. Sixty-four specimens from 64 dogs were histologically classified as perianal gland adenoma (59.38%), perianal gland epithelioma (12.50%), and perianal carcinoma (28.13%). All samples are analyzed for PGP expression using immunohistochemistry, scoring for percentage positivity and intensity. Four cases (6.25%) have a positive expression of PGP with intense cytoplasmic staining. There was a significant difference in the PGP expression pattern among the groups (p=0.01). The expression of PGP may provide valuable insights into disease prognosis and prediction of clinical outcomes of chemotherapy treatment in dogs with perianal gland tumors